2018
DOI: 10.1038/s41598-017-17480-1
|View full text |Cite
|
Sign up to set email alerts
|

Tunable geometrical frustration in magnonic vortex crystals

Abstract: A novel approach to investigate geometrical frustration is introduced using two-dimensional magnonic vortex crystals. The frustration of the crystal can be manipulated and turned on and off dynamically on the timescale of milliseconds. The vortices are studied using scanning transmission x-ray microscopy and ferromagnetic resonance spectroscopy. They are arranged analogous to the nanomagnets in artificial spin-ice systems. The polarization state of the vortices is tuned in a way that geometrical frustration ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Investigations of spin-wave resonances in frustrated, artificial spin systems are not restricted to Ising-like systems. For example, coupled magnetic vortices arranged in a kagome geometry 116 display collective oscillation modes of the interacting vortex cores that are sensitive to an applied magnetic field. This system is particularly interesting because frustration leads to multiple vortex configurations, reflected by the resonant frequencies.…”
Section: Fast Dynamicsmentioning
confidence: 99%
“…Investigations of spin-wave resonances in frustrated, artificial spin systems are not restricted to Ising-like systems. For example, coupled magnetic vortices arranged in a kagome geometry 116 display collective oscillation modes of the interacting vortex cores that are sensitive to an applied magnetic field. This system is particularly interesting because frustration leads to multiple vortex configurations, reflected by the resonant frequencies.…”
Section: Fast Dynamicsmentioning
confidence: 99%
“…In the second regime, ranging from 20 to 120 Oe, we observe a distinct gap in the mode spectrum independent of the in-plane field angle. Typically, one can observe a decrease of the resonant frequency in this field range, followed by the nucleation of magnetic vortices in the disks accompanied by the onset of a gyrotropic motion of the vortices 33 . The gyrotropic motion typically occurs at frequencies well below 1 GHz (depending on the dimensions of the disks and specific material parameters).…”
Section: Resultsmentioning
confidence: 99%
“…There are two reasons for this, both of which arise from the smaller thickness and lateral dimensions of our sample compared to the honeycomb disks studied in Ref. [33]. First, since vortex dynamics generally produce a weak signal, less thickness can make the signal detection more challenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that the dynamics in an array of magnetic disks can be used for spin-pumping applications 25 . Furthermore, it was shown that a spinice network made of interacting magnetic microdisks has a controllable ground state, depending on the excitation frequency 26 .…”
Section: Introductionmentioning
confidence: 99%